Designing a Fun English Vocabulary Card Application as a Means of Learning English Vocabulary for Elementary School Students - Setyawan, Haris; Arighi, Radityo Anindito; Isnanda, Reza Giga (Universitas Muhammadiyah Yogyakarta, 2020)
English has been globally used for communication and studied by almost all countries. Therefore, understanding and being able to communicate in English is crucial. A lot of English learning is currently delivered using the lecture method, but there is no medium for learning English vocabulary in an application. This study aims to create a Fun English Vocabulary Card game to improve children’s English vocabulary. To design the learning model, the design of use case and activity diagrams was utilized. Based on the pre-test and post-test results, this game significantly increased children’s English vocabulary. The average pre-test score was 43.625, and the average post-test score was 95, which indicates that the educational game application could improve users’ knowledge and understanding of English vocabulary.